Automotive FDI in emerging Europe : shifting locales in the motor vehicle industry - Jacobs, Andrew James, 1963- (Palgrave Macmillan, 2017)
This book examines the dramatic increase in automotive assembly plants in the former Socialist Central European (CE) nations of Czechia, East Germany, Hungary, Poland, and Slovakia from 1989 onwards. Enticed by relatively lower-wage labour and significant government incentives, the world's largest automakers have launched more than 20 passenger car assembly complexes in CE nations, with production accelerating dramatically since 2001. As a result, the annual passenger car production in Western Europe declined by more than 20% between 2001 and 2015, and alternatively in the CEE it increased by nearly 170% during this period. Drawing on case studies of 25 current and former foreign-run assembly plants, the author presents a rare historical account of automotive foreign assembly plants in the CE following this dramatic geographic shift. This book will expand the knowledge of policy-makers in Europe in relation to their pursuits of FDI and will be of great interest to scholars and students of business, economic history, political science, and development.- Resumé vydavatel
Keywords: automobilový průmysl -- Evropa střední a východní; zahraniční investice; automobile industry -- Europe, Central and Eastern; foreign investments; elektronické knihy; monografie; electronic books; monographs